2020
DOI: 10.1101/2020.09.10.289090
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inflammatory response in hematopoietic stem and progenitor cells triggered by activating SHP2 mutations evokes blood defects

Abstract: SummaryThe RASopathy Noonan syndrome (NS) is a frequent developmental disorder predominantly caused by activating mutations in the phosphatase SHP2. Among other features, NS children are predisposed to develop juvenile myelomonocytic leukemia (JMML). We developed a zebrafish mutant line carrying the NS-patient associated mutation Shp2-D61G. Shp2D61G zebrafish recapitulate major NS traits, including a JMML-like phenotype originating from defective hematopoietic stem and progenitor cells (HSPCs). Single cell RNA… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…A better understanding of the pathophysiology of NS and other RASopathies has also highlighted specific defects at the subcellular, cellular, or tissue levels that may represent potent targets for selective therapies. Thus, recent preclinical studies in mouse and zebrafish models of NS have shown constitutive inflammation as a driving force for metabolic impairment and haematological features [3], and treatment of zebrafish embryos with the antiinflammatory corticosteroid dexamethasone improved the JMML phenotype [48]. In addition, dysfunctions of mitochondrial bioenergetics and quality control have been identified in several RASopathies, including NS and Costello syndrome, that are causally linked to heart disease [49,50].…”
Section: Pathophysiology-driven Approachesmentioning
confidence: 99%
“…A better understanding of the pathophysiology of NS and other RASopathies has also highlighted specific defects at the subcellular, cellular, or tissue levels that may represent potent targets for selective therapies. Thus, recent preclinical studies in mouse and zebrafish models of NS have shown constitutive inflammation as a driving force for metabolic impairment and haematological features [3], and treatment of zebrafish embryos with the antiinflammatory corticosteroid dexamethasone improved the JMML phenotype [48]. In addition, dysfunctions of mitochondrial bioenergetics and quality control have been identified in several RASopathies, including NS and Costello syndrome, that are causally linked to heart disease [49,50].…”
Section: Pathophysiology-driven Approachesmentioning
confidence: 99%